Strategic Trading in Informationally Complex Environments - Lambert, Nicolas S.; Ostrovsky, Michael; Panov, Mikhail (Econometrica, 2018)
We study trading behavior and the properties of prices in informationally complex markets. Our model is based on the single‐period version of the linear‐normal framework of Kyle (1985). We allow for essentially arbitrary correlations among the random variables involved in the model: the value of the traded asset, the signals of strategic traders and competitive market makers, and the demand from liquidity traders. We show that there always exists a unique linear equilibrium, characterize it analytically, and illustrate its properties with a number of applications. We then use this characterization to study the informational efficiency of prices as the number of strategic traders becomes large. If liquidity demand is positively correlated (or uncorrelated) with the asset value, then prices in large markets aggregate all available information. If liquidity demand is negatively correlated with the asset value, then prices in large markets aggregate all information except that contained in liquidity demand.